Faithless In Death : In Death #52 - Robb, J. D., 1950- (New York : St. Martin's Press, 2021)
"In the new Eve Dallas police thriller from the #1 New York Times bestselling author J.D. Robb, what looks like a lover's quarrel turned fatal has larger-and more terrifying-motives behind it"--.
Keywords: Mystery fiction; Suspense fiction